Current stock situation and measures for the management and conservation of minke whales (Balaenoptera acutorostrata) in Korean waters. (January 2016) - Song, Kyung-Jun
Abstract: Although minke whales in Korean waters have been protected for more than 28 years after a commercial whaling moratorium in 1986, relatively little effort has been focused on assessing their current status of this population in this area after this protection and the efficacy of this protection. Thus, current stock situation and measures for the management and conservation of minke whales in Korean waters was investigated. Although Korea has undertaken significant efforts to archive the biological material of bycaught minke whales, the results remain incomplete. Furthermore, although a number of studies have reported the extent of bycaught minke whales, there has been little effort to reduce this occurrence in Korean waters compared with efforts to report it. Finally, there exists little data for investigating the effect of bycatch on the survival of minke whales in Korean waters. To improve weaknesses in the management of minke whales in Korean waters and to efficiently conserve and manage this population, the following efforts are urgently needed: 1) Conduct research on minke whales including satellite tagging; 2) Establish DNA registers for all minke whale bycatch, market surveys and intensive control of illegal catch; 3) Assess the usefulness of several mitigation measures to reduce bycatch (pingers, fishing gear modifications and time-area closures), and apply these measures; 4) Assess the effect of bycatch on the survival of minke whales in Korean waters; 5) Reduce the incentive for bycaught minke whales and use it as research funds for minke whales and incentives for releasing entrapped or entangled whale in fishing gears; 6) Compare with other studies on the management suggestions to modify the current stock situation. Among these suggestions to modify the current stock situation, the application of bycatch mitigation measures and intensive control of illegal catch are expected to efficiently improve the current stock situation of minke whales in Korean waters by reducing bycatch and illegal catch. Particularly, among bycatch mitigation measures, fishing gear modification and pinger are considered as efficient management suggestions for this stock in this area. Highlights: Discuss sustainable management on minke whales in Korean waters. Explain possible factors that challenge the sustainable management on minke whales in Korean waters. Encourage sustainable management on minke whales in Korean waters.